Probiotic Effect Of Wild Species Of Bacillus Spore Formers And Its Effect On Enteric Pathogens - ANU P SEBASTIAN; T R KEERTHI (International Journal of Pharma and Bio Sciences, 2012)
Wild species of Bacillus spore formers were selectively isolated from various sources like Dry spices, Milk, Soil, Intestine of pig and Chicken .Probiotic potential of isolates were studied on the basis of non hemolysis, non lecithinase activity ,acid bile tolerance, resistance to artificial gastric and intestinal fluids and antagonistic action towards enteric pathogens such as Salmonella typhi, Salmonella paratyphi A ,and Vibrio cholera. Based on probiotic qualities five strains were further selected and their antagonistic principles and susceptibility to commonly used antibiotics were studied.Among the five isolates Bacillus spp BM-3 from milk showed remarkable probiotic and antagonistic properties. Antimicrobial compound produced by BM-3 was heat labile and was not affected by the proteases. This isolate was susceptible to commonly prescribed antibiotics in conflict that they would not donate resistance. Biochemical identification reveals that the potential probiotic isolate bacillus spp BM-3 from milk is Bacillus subtilis and it can be studied In vivo for future development of potential probiotic